Perspectives of Students Towards Open Distance Learning: A Case Study of Bank Rakyat Staff Enrolled in UUM PJJ Program - Abd Aziz, Noriza (Universiti Utara Malaysia, 2022)
Purpose – The purpose of this paper is to examine whether perceived usefulness, perceived ease of use and perceived self-efficacy are able to influence Bank Rakyat sponsored staff enrolled in UUM PJJ Program’s behavioural intention to choose open distance learning (ODL). Design/Methodology/Approach – Technology Acceptance Model (Davis, 1989) had been identified to support the research framework of the study. Thus, a research framework was proposed in which three hypotheses were developed. Data was obtained from 125 respondents from Bank Rakyat sponsored staff enrolled in UUM PJJ Program using a convenient sampling. The data were analyzed by SPSS statistical program on descriptive statistics, factor analysis and regression. Findings – Results revealed that perceived usefulness and perceived self-efficacy have direct relationships with behavioural intention to choose open distance learning. Therefore, perceived usefulness and perceived self-efficacy influence Bank Rakyat sponsored staff enrolled in UUM PJJ Program to choose ODL. Meanwhile, perceived ease of use has no direct relationship with behavioural intention to choose open distance learning. Therefore, perceived ease of use cannot attract the interests and attentions to influence Bank Rakyat staff to use ODL. Moreover, perceived self-efficacy would not affect Bank Rakyat staff to choose ODL. Factor Analysis was conducted and revealed two dimensions of Perceived usefulness, namely PUTechnology Acceptance and PU-Performance Outcome. Factor Analysis also revealed two dimensions of ODL, namely ODL-Desire and ODL-Expectation. PUTechnology Acceptance and PU-Performance have direct relationships with ODLDesire. Likewise, PU-Technology Acceptance has a direct relationship with ODLExpectation. However, the relationship between PU-Performance and ODLExpectation is rejected. Practical implications – Study will help uncover significant understanding of students’ acceptance of ODL for UUM to develop further PJJ programs related to Islamic Finance and Banking course under Massive Open Online Courses (MOOC). Furthermore, ODL provides new opportunities for interaction and communication between students and lecturer through information and communication technology (ICT) and multimedia. Originality/Value – This study provides further empirical support of the behavioural intention are able to be influenced to choose ODL.